TROPICAL PEATLAND FOREST RESTORATION AS A CARBON EMISSION MITIGATION STRATEGY IN INDONESIA - Cedric Butler; Veronica Smith; Wayne Miller (Yayasan Adra Karima Hubbi, 2026)
Tropical peatland forests in Indonesia have been significantly impacted by deforestation, draining, and conversion to agricultural land, leading to large-scale carbon emissions. As one of the world’s largest peatland areas, Indonesia’s tropical peatlands are crucial in regulating global carbon cycles. Restoration of these ecosystems presents a significant opportunity to mitigate carbon emissions, which are exacerbating climate change. This research aims to evaluate the effectiveness of tropical peatland forest restoration as a strategy for carbon emission reduction in Indonesia. The study employs a mixed-methods approach, combining field observations, remote sensing data, and carbon modeling to assess the carbon sequestration potential of restored peatland forests. Findings show that successful restoration of peatlands can result in the sequestration of up to 15 million tons of CO2 annually, with significant increases in both above-ground and below-ground biomass. Additionally, the research identifies key factors influencing restoration success, including water table management and native species replanting. The study concludes that tropical peatland forest restoration is a viable and effective strategy for carbon emission mitigation in Indonesia. The research emphasizes the need for policy support and long-term monitoring to ensure the sustainability of restoration efforts and their contribution to global climate change mitigation.